Integrating cleaning studies with industrial practice: case study of an effective cleaning program for a frozen meat patties SME factory - Khalid, Nurul Izzah; Sulaiman, Umi Suhaila; Nasiruddin, N. A.; Hadran, M. M.; Ab Aziz, Norashikin; Mahmud @ Ab Rashid, Nor Khaizura; Noor Hasnan, Noor Zafira; Taip, Farah Saleena; Sobri, Shafreeza (Elsevier, 2019)
Cleaning of process equipment is a necessity in the food industry. There is no standard cleaning program formulated for all food industries. Thus, in order to achieve economic objectives and to comply with food hygiene regulations, specific cleaning problems need to be solved to achieve an optimal solution. In this work, a cleaning program was proposed for a local frozen meat patties Small and Medium Enterprise (SME) factory, X. Several cleaning tools such as a portable cleaning unit and industrial cleaning brushes with different functionality were used to ensure the effectiveness of the cleaning program. The portable cleaning unit was used to evaluate the impact of water jet with different nozzle distances (10 cm and 20 cm), cleaning times (30 s and 120 s), and temperatures (35 °C and 65 °C) in reducing different foodborne pathogens (Escherichia coli, Listeria monocytogenes, and Salmonella enteritidis). Two places of food processing equipment with two different stainless steel surfaces were tested. First, a former of meat patties (mesh wire surface), and second, a mixer (smooth surface). The results were then compared with factory X's current cleaning program and have shown that this new cleaning program can achieve physical clean level and helped to reduce microorganism to non-detectable level (less than 2.0 CFU/cm2). For the evening cleaning, the suggested cleaning program is using the portable cleaning unit at 65 °C, 120 s, 10 cm nozzle distance, and 5.2 bar. For the morning cleaning before production, the same parameters are suggested except for the temperature which is slightly higher at 75 °C.